Hubungan antara Kadar Albumin dan Bilirubin Tehadap Fungsi Hati pada Pasien Rehabilitas NAPZA < 2 Tahun di RS Dr. Radjiman Widiodiningrat Lawang - Islamia, Nadia Rahma; Siska, Previta Zeizar Rahmawat; Widhaningrum, Nanda (Poltekkes Kemenkes Semarang, 2025)
Prolonged use of narcotics can cause damage to the liver, which plays a role in the metabolism and detoxification of harmful substances in the body. Impaired liver function due to narcotics use can affect albumin and bilirubin levels which can be indicators of liver damage. This study aims to determine the relationship between albumin and bilirubin levels in narcotics rehabilitation patients 2 years at Dr. Radjiman Widiodiningrat Lawang Hospital. A total of 11 pure narcotics patients, without the use of psychotic drugs. The research method used is descriptive qualitative with random sampling technique. The results showed that 82% of patients had normal albumin levels, and all patients showed normal bilirubin levels. Correlation test analysis showed no significant relationship between the length of narcotics consumption and albumin levels (r = 0.004, p 0.05), and no significant relationship between the length of rehabilitation and albumin levels (r = 0.413, p 0.05). In addition, no significant correlation was found between the duration of drug use and bilirubin levels (r=-0.226, p0.05), or between the duration of rehabilitation and bilirubin levels (r=0.214, p0.05). The results of the homogeneity test and data normality test indicate that the data are distributed homogeneously and normally. In conclusion, there is no significant relationship between albumin and bilirubin levels with the duration of drug use and rehabilitation.